PHOSPHORUS TRANSPORT MODEL IN SEGARA ANAKAN ESTUARY WATER, CILACAP - Darmiatun , Suryatri
Abstrack ABSTRACT Rivers surrounding Segara Anakan are sources of organic pollutant which is part of water organism nutrition source. The organic pollutant consists of N, P, S, C, and O. Segara Anakan water quality studies were using field observation technique, therefore, in this study using modelling techniques. The study area was the Southern length of Cibeureum river. The objectives of study are (1) to apply and test mathematical model of phosphorus transport model (finite segment) in Segara Anakan, (2) to identify phosphorus distribution in Segara Anakan. The modeling assumptions are : phosphorus input comes from point source, initial phosphorus input is conl inaus input, flow direction is only in longitudinal direction, water flow movement caused by tidal force from the mouth of estuary and river. In one dimension model flow from and to lateral rivers (Kayu Mati and Siburak river) are ignored, every segment represents uniform water condition, estuary is equal to straight canal. Phosphotus transport model is explicit finite segment model. Two dimensions model has different finite segment transport equation at the segments that are influenced by lateral sources. In conclusions (I) one dimension phosphorus transport finite segment model can be applied to point source canal with straight morphology, (2) two dimensions phosphorus transport finite segment numeric model more suitable to be applied than I dimension bus transport finite segment numeric model. The model test showed that one dimension correlation values (r high water (11W) 1 1.38, r low water (LW)1 0.03, r HW 2 .19, r LW 23.26) lower than two dimensions correlation values (r HW 1 .84, r LW 1=0.69, r 11W-2).26, r LW 2=0.34), (3) simulation phosphorus concentrations different to field phosphorus concentrations because of model limitation. One dimension deviation values at HW-1=0.8, LW 1=1.64, 11W -2A).54, LW- 2=11.30 and two dimensions deviation values at HW-l=1.13, LW-1=823, 11W- 2=7.79, LW-2=7.83.